THE PERFORMANCE OF DECENTRALIZED FOREST MANAGEMENT: THE STUDY OF RUFIJI DISTRICT COUNCIL IN TANZANIA (Journal of Governance and Development (JGD), 2021)
Over the past two decades, the forest management services in Tanzania were decentralized to local government for the purpose of increasing its efficiency but the current evaluations show that the delivery of the services does not meet the standards and expectations set at the beginning. The goal of this article is to explore the performance of decentralised forest management and the extent to which institutional nexus: formal rules, policies, guidelines, and informal social rules affect the behaviour of local government officials involved in forest management at different levels. Based on the nature of this research, the qualitative approach was adopted with Rufiji district council as a case study. The actual research began with data collection through documentary reviews and in-depth interviews with 80 forest management officials at different levels and harvesters. The research shows that the number of institutional factors such as legal and policy framework, accountability framework and social rules particularly corruption affects the behaviour of forest officials, the community and other stakeholders involved in forest management at Rufiji district council.